Mapping Telehealth Interventions Supporting Self-Management in Coronary Artery Disease: Characteristics, Outcomes, and Evidence Gaps—A Scoping Review - Hendriyani, Desy; Pahria, Tuti; Purba, Chandra Isabella Hostanida; Fauzan, Naufal Hafizh (Journal of Applied Nursing and Health, 2026)
Background: Coronary artery disease (CAD) remains a major cause of morbidity and mortality worldwide, requiring long-term self-management to prevent recurrent cardiovascular events. Telehealth has emerged as a promising approach to support self-management through remote monitoring, education, lifestyle modification, and patient–provider communication. This scoping review aimed to map and synthesise the available evidence on telehealth-supported self-management interventions and their outcomes among adults with CAD. Methods: This scoping review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines and the Arksey and O’Malley framework refined by the Joanna Briggs Institute (JBI). Guided by the Population–Concept–Context (PCC) framework, literature searches were conducted in PubMed, ScienceDirect, Scopus, and EBSCOhost for studies published between 2016 and 2026. Four reviewers independently screened titles, abstracts, and full texts against predefined eligibility criteria. Data were charted using a structured extraction form, and methodological quality was appraised using JBI critical appraisal tools. Findings were synthesised using descriptive evidence mapping and narrative descriptive analysis. Results: Following the screening and eligibility assessment, 17 studies met the inclusion criteria and were included in the final synthesis. The included studies described a wide range of telehealth-supported self-management interventions, including mobile health applications, web-based platforms, telemonitoring systems, wearable devices, text messaging programs, cardiac telerehabilitation, and artificial intelligence-assisted technologies. Narrative descriptive synthesis showed that interventions commonly incorporated self-management components, including physical activity promotion, medication adherence support, dietary modification, smoking cessation, symptom monitoring, and psychosocial support. Across studies, reported outcomes included improvements in self-efficacy, health literacy, physical activity, medication adherence, quality of life, cardiovascular risk-factor management, and selected clinical indicators. Common intervention characteristics included personalized feedback, remote monitoring, nurse-led support, and multidisciplinary collaboration. The evidence also highlighted gaps related to long-term sustainability, implementation in resource-limited settings, digital equity, and adaptation across diverse healthcare contexts. Conclusion: This scoping review mapped the current evidence on telehealth-supported self-management for adults with CAD and demonstrated substantial diversity in intervention modalities, self-management strategies, and reported outcomes. The findings highlight important knowledge gaps related to implementation, sustainability, and equity, particularly in low-resource settings. Future research should prioritize implementation-focused studies, culturally adaptable telehealth models, and long-term evaluations to support the integration of telehealth into secondary prevention and CAD management